Akuntabilitas dan Transparansi Laporan Keuangan Terhadap Keputusan Membayar Zakat dengan Kepercayaan Sebagai Variabel Intervening - Sitti Marwa Kharie; Sahril R Torano (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The main objective of this research is to answer the problem formulation of whether transparency and accountability of financial reports influence payment decisions at Amil Zakat Infaq and Shaddaqah (LAZIS) institutions in Ternate City. This research was also conducted to test whether trust can be a moderating variable between transparency and accountability of financial reports and influencing zakat payment decisions. A quantitative approach was used to answer the research objectives. Primary data was collected by distributing questionnaires online and offline to muzaki, who pay zakat through LAZIS, which the government manages in Ternate City. A total of 185 samples were collected during the research period. Variance-based partial least squares structural equation modelling (PLS-SEM) was used for data analysis using SmartPLS. The research results show that trust is an essential variable influencing Muzaki's decision to pay zakat in LAZIS Ternate City with (β 0.558, t 9.671, p-value 0.000). Accountability is proven to influence Muzaki's trust with (β 0.271, t 3.641, p-value 0.000). Transparency was also proven to significantly influence Muzaki's trust with (β 0.185, t 2.523, p-value 0.012). An interesting finding from this research is that accountability and transparency do not directly influence the decision to pay zakat but have an indirect influence, namely through trust.